Penerapan Model Project Based Learning (PjBL) Flipped Classroom Berbantuan Artificial Intelligence (AI) pada Keterampilan Menulis Teks LHO - Dian Sarmita; Zulmi Aryani (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The purpose of writing is to enable readers to understand, comprehend, and comprehend the values ​​contained in a text, thus enabling them to think, express opinions, or act on the content. The chosen learning model can help students become more active in learning and not solely teacher-centered. In this case, the researcher chose a project-based learning model to be applied to the writing skills of junior high school students. The object of this study was the writing skills of eighth-grade students on observational report texts. This research provides a new contribution to the importance of implementing the Project-Based Learning model through an Artificial Intelligence-assisted Flipped Classroom on observational report text writing skills. The purpose of this study was to determine the effect of the project-based learning model through an artificial intelligence-assisted flipped classroom on observational report text writing skills. This study used a sample of eighth-grade junior high school students in South Solok Regency. Quantitative data analysis in this study used ANOVA to test the hypothesis. Before the data were tested with ANOVA, prerequisite tests were conducted, namely normality and homogeneity tests. In this study, the significance value of Levene's Test = 0.01 (<0.05), therefore, the first row (equal variances assumed) was used. Based on the results of the t-test on the equal variances assumed row, the Sig. (2-tailed) value was obtained at 0.01 (<0.05). This means that there is no significant difference between the writing skills of observation report texts (LHO) of students in experimental class 1 and experimental class 2. The Mean Difference value of 18.503 is positive, which indicates that the writing skills of observation report texts (LHO) of students in experimental class 1 are not much different from those in experiment 2.